(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Accidents are an intentional act which is not a voluntary act done by the people. Accidents, tragically, are not often due to ignorance, but are due to carelessness, thoughtlessness and over confidence [1]. Human, vehicle and environmental factors play roles before, during and after a trauma event. Accidents, therefore, can be studied in terms of agent, host and environmental factors and epidemiologically classified into time, place and nature of injury.